2022
DOI: 10.1021/acsami.1c21223
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Fast, and Scalable Reverse-Offset Printing of Micropatterned Copper Nanowire Electrodes with Sub-10 μm Resolution

Abstract: Copper nanowires (CuNWs) possess key characteristics for realizing flexible transparent electronics. High-quality CuNW micropatterns with high resolution and uniform thickness are required to realize integrated transparent electronic devices. However, patterning high-aspect-ratio CuNWs is challenging because of their long length, exceeding the target pattern dimension. This work reports a novel reverse-offset printing technology that enables the sub-10 μm high-resolution micropatterning of CuNW transparent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…To transfer the semidry film from the silicone blanket to the cliché or the target substrate without any residue, the AgNP/AgNW hybrid ink must have an adequate cohesive force that is greater than the adhesion between the blanket and semidry film and lower than the adhesion between the cliché and semidry film. , The cohesive force of the ink was finely tuned by adjusting the relative proportions of PGMEA, polyacrylate-based binder, and polyurethane (PU) diol. Moreover, the AgNP/AgNW hybrid ink must exhibit stronger tackiness than the AgNW ink, which has an inherent cohesion owing to its structural properties, such as wire entanglement.…”
Section: Resultsmentioning
confidence: 99%
“…To transfer the semidry film from the silicone blanket to the cliché or the target substrate without any residue, the AgNP/AgNW hybrid ink must have an adequate cohesive force that is greater than the adhesion between the blanket and semidry film and lower than the adhesion between the cliché and semidry film. , The cohesive force of the ink was finely tuned by adjusting the relative proportions of PGMEA, polyacrylate-based binder, and polyurethane (PU) diol. Moreover, the AgNP/AgNW hybrid ink must exhibit stronger tackiness than the AgNW ink, which has an inherent cohesion owing to its structural properties, such as wire entanglement.…”
Section: Resultsmentioning
confidence: 99%
“…Screen printing, gravure printing, spray-coating, and other non-digital printing methods can be done at high speed using a mask, but the disadvantage is that it is difficult to achieve high-resolution manufacturing (<10 μm). Recently, Kim et al reported a reverse-offset printing technology, 151 in which CuNWs were coated by Mayer rod and then transferred to a gravure plate. They used a commercial adhesive hand-roller to achieve the directional transfer of patterned ink to obtain CuNW patterns with a minimum line width of 7 μm.…”
Section: Printing and Sintering Methodsmentioning
confidence: 99%
“…[144][145][146] Table 2 lists the materials, capping agents, sintering methods, aspect ratio, and resistivity of some CuNWs inks. The hydrothermal method generally uses deionized water as the reaction medium, with hexadecylamine (HDA), [147][148][149][150][151] ethylenediamine (EDA), [152][153][154] octadecylamine (ODA) [155][156][157] and PVP 69,158,159 as the limiting ligand. By controlling the heating temperature, limiting ligand concentration and reaction time, CuNWs with different lengths and diameters can be obtained (Fig.…”
Section: Copper Nanowire Inkmentioning
confidence: 99%
“…Although existing transfer printing can be compatible with various materials, it fails to offer high-resolution/quality patterning. Kim et al proposed a novel reverse-offset printing technology by patterning sub-10 µm copper nanowire (CuNW) transparent conducting electrodes [80] . The intaglio trench allows only the desired pattern to remain on the stamp, without any morphological changes [Fig.…”
Section: Soft Lithographymentioning
confidence: 99%